GLUE EMBOLIZATION FOR TREATMENT OF RENAL INJURY - PEUNGJESADA, SILANATH; CHUROJANA, ANCHALEE; CHATIYASOOT, WALLAILAK (The ASEAN Journal of Radiology, 2023)
PURPOSE : To evaluate the outcome of glue embolization in two patients with renal AVF with and without pseudoaneurysm, one caused by percutaneous stone removal from the kidney and another one by trauma. MATERIALS AND METHODS : History taking, physical examination and laboratory investigation were reviewed for patient evaluation. Then angiography of the pathologic kidneys were performed. It showed outpouching of contrast media and rapid draining vein which was connected to adjacent artery. Afterthat embolization was done with optimal mixture of glue and lipiodol. RESULTS : Successful glue embolization of renal AVF and renal AVF with pseudoaneurysm of the kidneys with total occlusion of the affected vessels. Some degree of renal parenchyma infarction were seen without late complication. CONCLUSION : Endovascular treatment is still useful in the treatment of renal AVF and pseudoaneurysm. Because it is a kidney-conservative therapy and provides less drastic,less invasive, less expenses and short hospitalization. Alternative embolized material is glue although coil is recommended to be the material of choice. JAN. - APR. 2002. Volume VIII NumberI The result of treatment is excellent when it is held in experienced hand.